Technical opportunities to reduce global anthropogenic emissions of nitrous oxide. (9th January 2018) - Winiwarter, Wilfried; Höglund-Isaksson, Lena; Klimont, Zbigniew; Schöpp, Wolfgang; Amann, Markus
Abstract: We describe a consistent framework developed to quantify current and future anthropogenic emissions of nitrous oxide and the available technical abatement options by source sector for 172 regions globally. About 65% of the current emissions derive from agricultural soils, 8% from waste, and 4% from the chemical industry. Low-cost abatement options are available in industry, wastewater, and agriculture, where they are limited to large industrial farms. We estimate that by 2030, emissions can be reduced by about 6% ±2% applying abatement options at a cost lower than 10 €/t CO2 -eq. The largest abatement potential at higher marginal costs is available from agricultural soils, employing precision fertilizer application technology as well as chemical treatment of fertilizers to suppress conversion processes in soil (nitrification inhibitors). At marginal costs of up to 100 €/t CO2 -eq, about 18% ±6% of baseline emissions can be removed and when considering all available options, the global abatement potential increases to about 26% ±9%. Due to expected future increase in activities driving nitrous oxide emissions, the limited technical abatement potential available means that even at full implementation of reduction measures by 2030, global emissions can be at most stabilized at the pre-2010 level. In order to achieve deeper reductions in emissions, considerable technological development will be required as well as non-technical options like adjusting human diets towards moderate animal protein consumption.